The role of grit in inclusive education: a study of motivation and achievement among preservice physical education teachers - Lee, Joonyoung; Park, Jinwoo (Frontiers in Psychology, 2024)
Introduction: Grit, a combination of enduring effort and persistent interest, is key to long-term goals. The training of preservice physical education (PE) teachers is vital for child development, emphasizing the need to assess their resilience and commitment. However, research is limited regarding how grit influences motivation and achievement goals in PE. The purpose of this study was to explore how the grit dimensions of preservice PE teachers impact their motivation and achievement goals, which may subsequently shape their future career intentions of becoming PE teachers.Methods: A total of 279 preservice physical education (PE) teachers (69.5% males; 26.9% PE graduate program) from five South Korean universities participated in the study. They completed validated questionnaires measuring grit, motivation, achievement goal orientations, and career intentions. Descriptive statistics, correlation analysis, and structural equation modeling (SEM) were used to examine variable relationships and test the hypothesis model.Results: Correlation analysis indicated a spectrum of relationships between facets of grit (perseverance of effort and consistency of interests), motivational parameters, and career intention, with both positive and negative correlations ranging from weak to moderate (r ranging from .119 to .425, p < .05-.01). SEM confirmed the model's goodness-of-fit (χ2/df = 1.928, RMSEA = .058, IFI = .92, TLI = .91, CFI = .92). Path analysis showed that both perseverance of effort and consistency of interests significantly influenced motivational mechanisms (β ranging from -.34 to .57, p < .05-.01), both directly and indirectly, which then notably impacted career intentions (β = .10, p < .05). Notably, both grit dimensions significantly impacted mastery approach goals (β ranging from .49 to .56, p < .01). Mastery approach goals, in turn, had a substantial impact on intrinsic motivation (β = .27, p < .01), which subsequently significantly influenced career intentions (β = .32, p < .01).The study illuminated the complex relationships between grit dimensions, motivation, achievement goals, and career intentions of future PE teachers. SEM validation confirmed grit's direct and indirect influence on goal orientations and motivation, underscoring the importance of 1 incorporating grit-building strategies alongside mastery approach goals in preservice PE programs to enhance resilience, dedication, and long-term career commitment.